IMPLEMENTASI MODEL PEMBELAJARAN PIRAMIDA DALAM MENJALIN INTERAKSI POSITIF GURU DAN SISWA DI TK PGRI TUNAS 83 - Arrobi, Jimatul; Toni Sonjaya; Rustiani; Siti Rahmawati; Dede Ayu Lestari (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
Positive interaction between teachers and students is key to enhancing the development of children's brain synapses during the golden age. The purpose of this study is to explain how the Teaching Pyramid Model (TPM) is applied at TK PGRI Tunas 83 to create positive interactions between teachers and students. The main issues underlying this study are the still-dominant egocentric attitudes, lack of independence, and lack of student discipline in interactions. This research was conducted using a qualitative descriptive approach and a case study. Data were collected through documentation of learning strategies that utilize sensory, emotional, and environmental stimulation, as well as participatory observation. The research results show that the use of basic TPM levels through care and responsive interactions supported by an inclusive classroom environment successfully reduces interaction conflicts. It has been proven that using number pyramids (dice games) and sensory media (texture exploration) can increase interaction activity, counting skills, and children's critical thinking abilities. According to neuroscience-based developmental analysis, this supportive learning environment has the ability to provide emotional stability and cognitive readiness to students. The research results indicate that TPM is an integral approach that is useful for building discipline character and good social interactions in early childhood education.